Accuracy Assessment and Comparison of National, European and Global Land Use Land Cover Maps at the National Scale - Fonte, Cidália C. (2024)
Fonte, C. C., Duarte, D., Jesus, I., Costa, H., Benevides, P., Moreira, F., & Caetano, M. (2024). Accuracy Assessment and Comparison of National, European and Global Land Use Land Cover Maps at the National Scale: Case Study: Portugal. Remote Sensing, 16(9), 1-34. Article 1504. https://doi.org/10.3390/rs16091504 --- The study has been partly supported i) Compete2020 (POCI-05-5762-FSE-000368), supported by the European Social Fund, and ii) Fundação para a Ciência e a Tecnologia, Portugal (FCT) under project grants UIDB/00308/2020 (DOI: 10.54499/UIDB/00308/2020)—Instituto de Engenharia de Sistemas e Computadores de Coimbra (INESCC)- and UIDB/04152/2020—Centro de Investigação em Gestão de Informação (MagIC).